Dysregulation of MMP2-dependent TGF-ß2 activation impairs fibrous cap formation in type 2 diabetes associated atherosclerosis - Singh, Pratibha; Sun, Jiangming; Cavalera, Michele; Al-Sharify, Dania; Matthes, Frank; Barghouth, Mohammad; Tengryd, Christoffer; Dunér, Pontus; Persson, Ana; Sundius, Lena; Nitulescu, Mihaela; Bengtsson, Eva; et al. (Lund University, 2024)
Cohort description:

Human carotid plaques used in this study were obtained from the Carotid Plaque Imaging Project biobank (Malmö, Sweden; ClinicalTrials.gov ID NCT05821894). These plaques were collected from patients undergoing carotid endarterectomy (CEA) at Skåne University Hospital's Vascular department in Malmö, Sweden. The indications for surgery were: plaques associated with ipsilateral symptoms (transitory ischemic attack, stroke, or amaurosis fugax) and a degree of stenosis greater than 70% (measured by duplex ultrasound), or plaques from asymptomatic patients, with a degree of stenosis greater than 80%. The study has received ethical approval, and all patients provided oral and written informed consent. All work involving human subjects adheres to the principles of the 1975 Declaration of Helsinki.

Dataset description:

- Bulk RNA sequencing was performed on carotid plaques from patients with type 2 diabetes (T2D). Total RNA was extracted with the Trizol method, and libraries were prepared using the ScriptSeq™ v2 Kit. Sequencing was performed on Illumina HiSeq2000 and NextSeq platforms. Reads were aligned to the GRCh38 genome with STAR and quantified using Salmon with GENCODE V27 annotations. Counts were normalized with edgeR and expressed as log2-transformed counts per million (CPM) after batch corrected for sequencing platforms.
- Single-cell transcriptomes were generated from human atherosclerotic plaque cells. Live cells were stained for CD45 and FACS sorted into 384-well plates, separating CD45+ and CD45- populations. RNA libraries were prepared and sequenced using the SmartSeq2 protocol at the SciLife Eukaryotic Genomics Facility. Cells with fewer than 10,000 raw reads, fewer than 500 detected genes, or more than 15% ERCC RNA Spike-In were excluded. Counts were log-normalized, scaled, and the top 2000 highly variable genes were used for dimensional reduction.
- Spatial transcriptomics was performed on 10µm carotid plaque sections using the Visium Spatial Gene Expression Slide & Reagent Kit (PN-1000184) and the standard protocols (CG000239 RevD,10x Genomics, Pleasanton, CA, USA). Libraries were sequenced on the NextSeq 500/550 platform with the High Output Kit v2.5 (150 cycles) at a depth of 400 million read pairs per sample. FASTQ files and corresponding histological images were processed with Space Ranger v1.0.0, using STAR v2.5.1b for genome alignment against the hg38 reference genome.


Data availability:

Current European data regulations preclude the open sharing of sensitive data from living humans, including genetic and sequencing data. The sequencing data used in this study can be accessed by making a reasonable request to the corresponding author, provided the legal terms for access are met.

Terms for access:

- The human data complies with GDPR regulations and is available, upon request, to qualified academic investigators solely for the purpose of replicating the procedures and findings outlined in the article.

- Access to the dataset is contingent upon successful completion of a data sharing agreement with the principal investigator (thus ensuring compliance with GDPR) as well as written approvals from the ethical review board of Sweden, Region Skåne, and Lund University, respectively.

- The existing ethical permit restricts the sharing of raw individual data due to its sensitive character, allowing only the sharing of aggregated data. Should researchers seek access to raw individual data, a separate written ethical approval and other legal requirements must be provided, in order for the request to be considered.

- Approved researchers must refrain from attempting to identify or contact individual study participants represented in the dataset. They may not generate information that could compromise participants' identities.

- Users are prohibited from using the datasets or any derivatives thereof for commercial purposes.

- Approved investigators are obligated to immediately report any unauthorised data sharing or breaches of data security on their behalf to the data access committee. Such reports should include comprehensive details to facilitate resolution and ensure data confidentiality.
Keywords: Cardiology (incl. cardiovascular diseases); Medical and Health Sciences; Medicin och hälsovetenskap; Cardiology and Cardiovascular Disease; Kardiologi och kardiovaskulära sjukdomar